Efektivitas SK. Gubernur Nomor : G/196/IV.02/HK/2006 Tentang Tim Penegakan Hukum Lingkungan Hidup Provinsi Lampung - Agus Iskandar (PRANATA HUKUM, 2013)
Environmental Enforcement Law Team in Lampung Provincy to Effort Industrial Waste Reduction as Impact from Firms Avaibility in Lampung Provincy. This research aims to know what Regent Policy to set up Environmental Law Enforcement Team in Lampung Provincy (team) can implementation effective.This research takes Lampung Provincy with empirical evaluative research. The collection data methods are field and reference study in which to obtain primary and secondary data. This research use qualitative data analysis This research gets conclution that implementation of the team which have been set up with decision letter of Lampung Provincy Number G/196/IV.02/HK/2006 on Mei 4th 2006 canât run effective. This matter can be seen from indicators of target matchness and working program realization, also from indicators of perception level and society responsiveness.